The Transformative Power of Love in John Williams's Stoner - Kyoung-Min Han; Yonghwa Lee (American Studies in Scandinavia)
This article examines the transformative power of love demonstrated by Stoner’s life in John Williams’s Stoner. Drawing on Jean-Luc Marion’s phenomenology of love, the essay contends that Stoner’s life, driven by love, is far from a failure. Stoner’s falling in love with literature can be seen as what Marion calls a “saturated phenomenon” in that it makes him transcend himself and have his being defined in relation to the alterity of the other. Stoner’s relationship with Katherine Driscoll is significant because it helps to resolve the separation of the mind and the senses caused by his love for literature. Through his relationship with Katherine, in which lust and learning become one process, Stoner recognizes love as an ongoing, continual process that involves the dynamic power of time. Realizing that he has given love to every moment of his life, he gives love even to his moment of death, which ironically becomes the most important moment of his celebration of life. Through his book, he seeks to continue to love loving beyond the moment of death and thereby defy death and non-being.